2020
DOI: 10.1111/jfbc.13489
|View full text |Cite|
|
Sign up to set email alerts
|

Bifidobacterium bifidumTMC3115 ameliorates milk protein allergy in by affecting gut microbiota: A randomized double‐blind control trial

Abstract: We aimed to explore the effects of Bifidobacterium bifidum TMC3115 intervention on cow's milk protein allergy (CMPA) and gut microbiota in infants. A total 256 CMPA infants were randomly and evenly assigned into an intervention group (B. bifidum) and a control group (placebo). Allergic scores, anti-inflammatory responses, and secondary outcomes were measured. Fecal specimens were collected, and the gut microbiota were analyzed by using 16S rDNA sequencing. After 6-month B. bifidum intervention, B. bifidum TMC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…According to the studies of Ma et al [37], probiotic microbes such as Bacillus subtilis, Saccharamyces cerevisiae, and Enterococcus faecalis can enrich milk secretion in cows and an inhibition of the milk allergy reaction was noted by the administration of Bifidobacterium bifidum [38]. Studies also showed that by stimulating GH/IGF-1 hormone, both Bacillus subtilis and Bacillus amyloliquefaciens can upgrade intestinal maturation and growth competency [39].…”
Section: Probiotics In Ruminant Nutrition and Healthmentioning
confidence: 99%
“…Modulation of the gut microbiota could also reduce the side-effects of COVID-19 vaccines. It has been shown that probiotics can effectively ameliorate allergy ( Jing et al, 2020 ). Several probiotics including B. longum , B. breve , L. plantarum , L. casei , L. fermentum and L. rhamnosus have been demonstrated to have anti-allergic effects through animal studies and clinical trials ( Shu et al, 2019 ).…”
Section: Approaches To Improve Gut Microbiota For Covid-19 Vaccinationsmentioning
confidence: 99%